Le Prince d’Albert Memmi, une tentative théâtrale sur le pouvoir et la domination - Hervé Sanson (Continents manuscrits)
Albert Memmi’s Le Prince is the unique trial of drama work the French-Tunisian sociologist and writer has undertaken so far, and which has not been edited yet. The principal problems raised in Memmi’s works are present in this draft : domination relationships first of all ; then class ones, but moreover : gender relations and therefore – female oppression. This theatrical attempt offers also a reflection about power’s nature – central theme of the novel Le Désert which is synchronic to Le Prince. Finally, the study of play’s genetic dossier reveals a very interesting perspective of what drama work and its visual dimension should be according to Memmi : a première.